2022
DOI: 10.1073/pnas.2118192119
|View full text |Cite
|
Sign up to set email alerts
|

Luxotonic signals in human prefrontal cortex as a possible substrate for effects of light on mood and cognition

Abstract: Studies with experimental animals have revealed a mood-regulating neural pathway linking intrinsically photosensitive retinal ganglion cells (ipRGCs) and the prefrontal cortex (PFC), involved in the pathophysiology of mood disorders. Since humans also have light-intensity–encoding ipRGCs, we asked whether a similar pathway exists in humans. Here, functional MRI was used to identify PFC regions and other areas exhibiting light-intensity–dependent signals. We report 26 human brain regions having activation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 98 publications
2
7
0
Order By: Relevance
“…This suggests that the amount of visible sky is the strongest predictor in the context of the other green space variables, which may be seen as arguing in favor of the idea that sunlight/brightness is the most prominent driving mechanism of the observed brain effects. Recent research demonstrating the light sensitivity of the prefrontal cortex in humans, might be interpreted to support this notion (Sabbah et al, 2022). The authors of this study state that their findings offer a functional link between light exposure and PFC-mediated cognitive and affective phenomena.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that the amount of visible sky is the strongest predictor in the context of the other green space variables, which may be seen as arguing in favor of the idea that sunlight/brightness is the most prominent driving mechanism of the observed brain effects. Recent research demonstrating the light sensitivity of the prefrontal cortex in humans, might be interpreted to support this notion (Sabbah et al, 2022). The authors of this study state that their findings offer a functional link between light exposure and PFC-mediated cognitive and affective phenomena.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, manipulation of the transmission of light signals to the mPFC alters depression-like behaviours in animals 10 , distinct light colours differentially decrease negative mood and increase amygdala-PFC connectivity in humans 11 , and bright light leads to enhanced fear extinction together with suppression of fear acquisition, both being accompanied by light-associated modulation of mPFC activity 12 . We have recently further reported activity corresponding with the intensity of light in several gross regions of the human mPFC 13 . The substrate of such correspondence however, i.e., an ability of mPFC neurons to encode light-intensity, remains unclear.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, an fMRI study has reported reduced PFC activity (including the subgenual anterior cingulate cortex and orbitofrontal gyrus) in response to light as a function of luminance level. The suppressed brain activity is similar to the impact of chemical antidepressants, which could indicate the anti-depressive role of light in the PFC subregions [ 161 ].…”
Section: Emotional Processing and Moodmentioning
confidence: 99%